Integrity of Amygdala Subregion-Based Functional Networks and Emotional Lability in Drug-Naïve Boys With ADHD. Issue 12 (October 2020) - Yu, Xiaoyan; Liu, Lu; Chen, Wai; Cao, Qingjiu; Zepf, Florian Daniel; Ji, Gongjun; Wu, Zhaomin; An, Li; Wang, Peng; Qian, Qiujin; Zang, Yufeng; Sun, Li; et al.
Objective: This study evaluated the functional networks of amygdala subregions (basolateral [BLA], centromedial [CMA], and superficial amygdala [SFA]) in ADHD and their association with emotional lability (EL) symptoms.Method: Resting-state functional connectivity (RSFC) of amygdala subregions and their correlations with EL scores were evaluated in 35 drug-naïve boys with ADHD and 30 age-matched healthy controls (HC).Results: Compared with HC, altered RSFC were detected differently for each amygdala subregion in ADHD: altered RSFC of BLA with the thalamus and vermis; aberrant RSFC of CMA with the superior temporal gyrus/pole and insula, precuneus and cerebellum; reduced RSFC of SFA with dorsal frontoparietal cortices. Within ADHD, higher EL scores were associated with reduced negative RSFC of SFA with the dorsolateral prefrontal cortex and inferior parietal lobe.Conclusion: Diffuse alterations of amygdala subregion-based networks are associated with ADHD, and the weaker SFA–frontoparietal networks might be involved in the hypothesized top–down effortful regulation of emotion.